An Insight into All Tested Small Molecules against Fusarium oxysporum f. sp. Albedinis: A Comparative Review - Kaddouri, Yassine; Benabbes, Redouane; Ouahhoud, Sabir; Abdellattif, Magda; Hammouti, Belkheir; Touzani, Rachid (Molecules (Basel, Switzerland), 2022)
Bayoud disease affects date palms in North Africa and the Middle East, and many researchers have used various methods to fight it. One of those methods is the chemical use of synthetic compounds, which raises questions centred around the compounds and common features used to prepare targeted molecules. In this review, 100 compounds of tested small molecules, collected from 2002 to 2022 in Web of Sciences, were divided into ten different classes against the main cause of Bayoud disease pathogen Fusarium oxysporum f. sp. albedinis (F.o.a.) with structure–activity relationship (SAR) interpretations for pharmacophore site predictions as (δ−···δ−), where 12 compounds are the most efficient (one compound from each group). The compounds, i.e., (Z)-1-(1.5-Dimethyl-1H-pyrazole-3-yl)-3-hydroxy but-2-en-1-one 7, (Z)-3-(phenyl)-1-(1,5-dimethyl-1H-pyrazole-3-yl)-3-hydroxyprop-2-en-1-one 23, (Z)-1-(1,5-Dimethyl-1H-pyrazole-3-yl)-3-hydroxy-3-(pyridine-2-yl)prop-2-en-1-one 29, and 2,3-bis-[(2-hydroxy-2-phenyl)ethenyl]-6-nitro-quinoxaline 61, have antifungal pharmacophore sites (δ−···δ−) in common in N1---O4, whereas other compounds have only one δ− pharmacophore site pushed by the donor effect of the substituents on the phenyl rings. This specificity interferes in the biological activity against F.o.a. Further understanding of mechanistic drug–target interactions on this subject is currently underway.